Authoritative Parenting Style on the Academic Resilience of Out-of-Town University Students - Porayouw, Gracia Virjini Juniarti; Sarajar, Dewita Karema (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Out-of-town university students often face academic pressure, adaptation difficulties, and challenges in adjusting to a new environment, which may affect their ability to cope with academic demands. Therefore, academic resilience becomes an important factor for students living away from home. This study aimed to examine the influence of authoritative parenting style on the academic resilience of out-of-town university students. The study employed a quantitative approach using simple linear regression analysis. The participants were 225 out-of-town university students aged 18–25 years selected through purposive sampling. Data were collected using the Parenting Styles and Dimensions and the Academic Resilience Scale-20. The findings revealed that authoritative Questionnaire parenting style had a positive and significant influence on academic resilience (Sig. = 0.005, p < 0.05). The positive regression coefficient (B = 0.050) indicates that higher levels of authoritative parenting style are associated with higher levels of academic resilience among out-of-town university students. These findings suggest that parenting characterized by warmth, open communication, and consistent discipline plays an important role in helping students cope with academic challenges while living away from home.Mahasiswa perantau sering menghadapi tekanan akademik, kesulitan adaptasi, serta tantangan dalam menyesuaikan diri dengan lingkungan baru yang dapat memengaruhi kemampuan mereka dalam menghadapi tuntutan akademik. Oleh karena itu, resiliensi akademik menjadi faktor penting bagi mahasiswa yang tinggal jauh dari keluarga. Penelitian ini bertujuan untuk mengetahui pengaruh pola asuh otoritatif terhadap resiliensi akademik pada mahasiswa perantau. Penelitian ini menggunakan pendekatan kuantitatif dengan analisis regresi linear sederhana. Partisipan penelitian berjumlah 225 mahasiswa perantau berusia 18–25 tahun yang dipilih menggunakan teknik purposive sampling. Pengumpulan data dilakukan menggunakan instrumen Parenting Styles and Dimensions Questionnaire dan Academic Resilience Scale-20. Hasil penelitian menunjukkan bahwa pola asuh otoritatif berpengaruh positif dan signifikan terhadap resiliensi akademik (Sig. = 0,005, p < 0,05). Koefisien regresi positif (B = 0,050) menunjukkan bahwa semakin tinggi penerapan pola asuh otoritatif, maka semakin tinggi pula resiliensi akademik pada mahasiswa perantau. Temuan ini menunjukkan bahwa pola asuh yang ditandai dengan kehangatan, komunikasi terbuka, dan disiplin yang konsisten berperan penting dalam membantu mahasiswa menghadapi tantangan akademik selama menjalani kehidupan jauh dari keluarga.